DOI: 10.31274/etd-180810-1635
|View full text |Cite
|
Sign up to set email alerts
|

Fish growth responses to a changing environment: effects of aquatic nuisance species and environmental conditons in a shallow, eutrophic lake

Abstract: 13 Introduction 14 Methods 17 Results 25 Discussion 28 Management Implications 35 References 36 APPENDIX 1. Size-specific growth curves for black bullhead in Clear Lake, Iowa. 64 APPENDIX 2. Size-specific growth curves for common carp in Clear Lake, Iowa. 65 APPENDIX 3. Size-specific growth curves for walleye in Clear Lake, Iowa. 66 APPENDIX 4. Size-specific growth curves for yellow bass in Clear Lake, Iowa. 67 APPENDIX 5. Fish collection data for fish collected in Clear Lake, Iowa. 68 APPENDIX 6. Age-length f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
0
4
0
1
Order By: Relevance
“…In contrast, forage availability and inter-and intraspecific competition might not be an issue in aquaculture systems (Noble et al 2007). The influence of temperature on fish growth has been widely studied; optimal temperatures for growth have been determined for several species (Pörtner et al 2001, Handeland et al 2008, Katzenmeyer 2010. In particular, an important factor affecting fish growth is stocking density; its effect on growth performance and yield has been studied extensively (Rieman and Myers 1992, Apu et al 2012, Long et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, forage availability and inter-and intraspecific competition might not be an issue in aquaculture systems (Noble et al 2007). The influence of temperature on fish growth has been widely studied; optimal temperatures for growth have been determined for several species (Pörtner et al 2001, Handeland et al 2008, Katzenmeyer 2010. In particular, an important factor affecting fish growth is stocking density; its effect on growth performance and yield has been studied extensively (Rieman and Myers 1992, Apu et al 2012, Long et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…La influencia de la temperatura en el crecimiento de los peces ha sido ampliamente estudiada. Se han determinado las temperaturas óptimas de crecimiento para varias especies (Pörtner et al 2001, Handeland et al 2008, Katzenmeyer 2010. En particular, un factor importante que afecta el crecimiento de los peces es la densidad de cultivo; su efecto sobre el crecimiento y el rendimiento se ha estudiado ampliamente (Rieman y Myers 1992, Apu et ).…”
Section: Discussionunclassified
“…In addition, ω, which is roughly equivalent to the product of L ∞ and k and corresponds to the growth rate near t 0 , was estimated and is recommended for statistical comparisons (Gallucci and Quinn ) because of the strong negative correlation of L ∞ and k . The original von Bertalanffy growth model can be reparameterized using ω, and the equation isLfalse(tfalse)=ω/kfalse[1ekfalse(tt0false)false]. The ω term was compared across time periods for each species using pairwise t ‐tests (Katzenmeyer ).…”
Section: Methodsmentioning
confidence: 99%
“…The ω term was compared across time periods for each species using pairwise t-tests (Katzenmeyer 2010). For Common Carp and Walleye the approach of Jackson et al (2008) and Quist et al (2003) was followed to convert lengths at age to the relative growth index (RGI).…”
Section: Fish Growth Changes In a Midwestern Lakementioning
confidence: 99%
“…A more recent experimental study using fluorescent markers demonstrated the formation of so-called lignes d'arrêt de croissance (Meunier andPascal 1981/1982), which provided a physiological basis for their use in a followup assessment of the growth of an individual cohort of carp (Jestin et al 1985). The dorsal spine has been used either as the sole ageing structure (Wichers 1976;Katzenmeyer 2010;Weber et al 2015) or, more often, in conjunction with others (Schoonover and Thompson 1954;Jackson 1955;Sandoz 1960;Starrett and Fritz 1965;Lubinski et al 1984;Colvin et al 2012) (Table S1 in Supporting Information). Different sectioning planes along the length of the dorsal spine have been shown to result in deviations in back-calculated growth from annuli (Wichers 1976).…”
Section: Dorsal Spinementioning
confidence: 99%